18F‐fludeoxyglucose positron emission computed tomography (18F‐FDG‐PET/CT) versus 68Ga‐DOTATATE‐PET/CT in patients with head and neck cancer: Comparisons and implications for treatment. Issue 2 (19th November 2022) - Patel, Rusha; Marano, Gary; Joseph, Joe; Chung, Jeffson; Plata, Andrew; Vos, Jeffrey A.
Abstract: Background: Tumor‐specific molecular imaging in head and neck squamous cell carcinoma (HNSCC) is not well established. Somatostatin receptors (SSTRs) are found in solid tumors, including HNSCC. 68 Ga‐DOTATATE, a commercially available radionuclide that binds SSTRs, may have utility in imaging HNSCC. Methods: Patients with HNSCC received pretreatment imaging with 18 F‐FDG‐PET/CT and 68 Ga‐DOTATATE. Imaging was compared for concordance. When available, surgical resection specimens were compared to pretreatment imaging findings. Historic HNSCC tumor specimens were assessed for both SSTR and p16/human papilloma virus (HPV) expression. Results: Twenty patients were imaged. Fifteen had oropharyngeal cancer. Primary tumor site was concordant between imaging modalities for all patients. One of 45 lymph nodes was discordant. Retrospective specimen review showed a significant correlation with SSTR expression and HPV/p16 expression. No adverse events occurred. Conclusions: 68 Ga‐DOTATATE imaging is safe and effective in HNSCC. SSTR expression may be increased in HPV‐mediated tumors. Targeted therapies to SSTR should be explored.